Adopting, Adapting, and Opting Out: State Response to Federal Voting System Guidelines. - Hale, Kathleen; Brown, Mitchell (Publius: The Journal of Federalism, 2013)
This article examines the state response to voluntary federal certification of electronic voluntary voting system guidelines (VVSGs) and current intergovernmental issues surrounding electronic voting systems across the country. Federal certification is not widespread, and most states have adapted modified methods of assuring system integrity or have opted out altogether. States that participate in VVSG have greater technological sophistication, higher levels of election administration professionalism, and are more likely to adopt touchscreen voting machines. Unlike other election administration reforms, VVSG does not appear to be linked to partisan political factors. Our findings have implications for understanding the limits of voluntary federal programs and the importance of technological capacity and professional human resources in American election administration.